Factors Affecting Human Resource Information Systems’ Effectiveness in the South African Public Health Sector - Udekwe, Emmanuel (Estudios de Administración, 2023)
Systems for managing human resources such as Human Resource Information Systems (HRIS) are thought of as change enablers that help organisations gain a competitive edge. The health sector has a significant need for efficient HR practices, which often stimulates several research projects. It is interesting to note that despite the focus of researchers and practitioners on the advantages of using an HRIS in the health sector, it is still not clear how this system can be used to its full potential to support workforce sustainability and retention in South Africa's public health sector. Based on this, the research seeks to determine why South Africa's public health sector has not yet adopted a successful HRIS. A partially integrated mixed-method research was conducted through a qualitative and a quantitative examination of the information gathered from four (4) selected hospitals in the Western Cape Province of South Africa. The questionnaire was completed by forty-six (46) persons, while forty-one (41) people were interviewed. According to the findings, an outdated HRIS named Persal is the HRIS used in the South African public health sector while organisational structures obstruct the system's complete deployment. The requirement of significantly addressing these organisational structural limitations in order to increase system utilisation and employee engagement is a key conclusion of our results with suggested ideas.